Feeding propionic acid-treated, flaked sorghum to finishing steers - Gugle, Terry L.; Fink, G.; Riley, Jack G. (Kansas State University. Agricultural Experiment Station, 2011)
Fifty-four yearling Hereford steers averaging 805 pounds were used in an 86-day finishing trial to determine the effect of adding low levels of propionic acid to steam flaked sorghum grain. Three treatments were examined. Treatment one consisted of sorghum grain steam flaked twice weekly for a maximum of 4 days between flaking. Treatment two was the same as treatment 1 except that propionic acid was added into the discharge auger at 0.15% of the weight of the flakes. Treatment three was flaking once a week with propionic acid added at 0.25% of the weight of the flakes. Both acid levels significantly (P<.05) improved gain and efficiency.
1776-1976 "Buffalo to Beef" is known as Cattlemen’s Day, 1976
Keywords: Beef; Propionic-acid; Gain; Efficiency; Steam flaked sorghum; Finishing steers